Power Domination and Resistance in Nawal El Saadawi’s Mawtu Ma’ali Al-Waziri Sabiqan: Antonio Gramsci’s Hegemony - Hidayat, Ridho; Rohanda, Rohanda; S, Dendi Yuda (Jurnal Adabiyah, 2025)
This research explores the dynamics of hegemony and resistance in Nawal El Saadawi’s novel Mawtu Ma‘ali al-Waziri Sabiqan through the lens of Antonio Gramsci’s theory of cultural hegemony. The research takes Gramsci’s concepts of ideological domination and counter-hegemonic struggle as its formal object, while the novel serves as the material object. Using a qualitative descriptive approach and a critical reading method grounded in ideological literary theory, this research positions itself within contemporary Arabic literary research that intersects with cultural-political analysis. The findings indicate that power in the novel operates not only through coercive mechanisms but also through ideological consent embedded within social institutions and dominant narratives that regulate behavior, identity, and voice. Resistance emerges as both symbolic and material acts of defiance that challenge the prevailing ideological structures. This research highlights literature as a site of negotiation between power and ideology, offering valuable insight for literary and cultural studies in understanding how texts mediate sociopolitical relations and contestations. ملخص تستكشف هذه الدراسة ديناميكيات الهيمنة والمقاومة في رواية نوال السعداوي "موت معالي الوزيري سابقان" من خلال منظور نظرية أنطونيو غرامشي في الهيمنة الثقافية. تتخذ هذه الدراسة مفهوم غرامشي للهيمنة الأيديولوجية والصراعات المضادة للهيمنة موضوعًا شكليًا لها، بينما تُمثل الرواية موضوعها المادي. باستخدام منهج وصفي نوعي وأساليب قراءة نقدية ترتكز على النظرية الأدبية الأيديولوجية، تضع هذه الدراسة نفسها ضمن البحث الأدبي العربي المعاصر المتقاطع مع التحليل الثقافي السياسي. تشير النتائج إلى أن القوة في الرواية لا تعمل فقط من خلال آليات الإكراه، بل أيضًا من خلال الموافقة الأيديولوجية المضمنة في المؤسسات الاجتماعية والسرديات السائدة التي تنظم السلوك والهوية والصوت. تبرز المقاومة كأفعال تحدٍّ، رمزية ومادية، تتحدى البنى الأيديولوجية السائدة. تُسلط هذه الدراسة الضوء على الأدب كساحة للتفاوض بين القوة والأيديولوجيا، مقدمةً رؤى قيّمة للدراسات الأدبية والثقافية في فهم كيفية توسط النصوص في العلاقات الاجتماعية والسياسية والصراعات Abstrak Penelitian ini mengeksplorasi dinamika hegemoni dan perlawanan dalam novel Mawtu Ma‘ali al-Waziri Sabiqan karya Nawal El Saadawi melalui lensa teori hegemoni budaya Antonio Gramsci. Penelitian ini mengambil konsep dominasi ideologis dan perjuangan kontra-hegemoni Gramsci sebagai objek formalnya, sementara novel berfungsi sebagai objek materialnya. Dengan menggunakan pendekatan deskriptif kualitatif dan metode pembacaan kritis yang berlandaskan teori sastra ideologis, penelitian ini memposisikan dirinya dalam penelitian sastra Arab kontemporer yang bersinggungan dengan analisis budaya-politik. Temuan menunjukkan bahwa kekuasaan dalam novel beroperasi tidak hanya melalui mekanisme koersif, tetapi juga melalui persetujuan ideologis yang tertanam dalam institusi sosial dan narasi dominan yang mengatur perilaku, identitas, dan suara. Perlawanan muncul sebagai tindakan pembangkangan, baik simbolis maupun material, yang menantang struktur ideologis yang berlaku. Penelitian ini menyoroti sastra sebagai arena negosiasi antara kekuasaan dan ideologi, menawarkan wawasan berharga bagi studi sastra dan budaya dalam memahami bagaimana teks memediasi hubungan dan kontestasi sosiopolitik.